The Beyond the Books Program: Improving Medical Student Attitudes Toward the Underserved - Aaron M. Briggs; Stephen Y. Wang; Subasish Bhowmik; Jacob Wasag; Roshini C. Pinto-Powell (Health Equity, 2018)
Purpose: To determine the impact of the Beyond the Books (BTB) program, a short-term pre-clinical intervention, on medical student attitudes toward the underserved (MSATU). Methods: BTB was evaluated through a prospective cohort study using the validated MSATU questionnaire. Results: There were no significant MSATU total score differences between BTB students (n=13) and student controls (n=29) at the beginning of the program. At the program's conclusion, BTB participant MSATU total scores were significantly higher than those of controls (p<0.001). Conclusion: Although limited by selection methods, our MSATU data support the capability of short-term pre-clinical interventions to significantly improve medical student attitudes toward underserved communities.